The Effect of Physical Activity on Elderly Woman with Rheumatoid Arthritis Symptoms - Yanusman, Ayuningtyas (Sports Medicine Curiosity Journal, 2023)
Rheumatoid Arthritis (RA) is an autoimmune disease that causes joint inflammation. Elderly, especially women are more susceptible to RA due to hormonal factors. RA patient often feel inconvenient during physical activity because of pain in their joint. The purpose of this study was to determine the effect of physical activity on elderly woman with Rheumatoid Arthritis. This research is a literature study using traditional review method. Journal article studies were searched in Google Scholar, OneSearch Indonesia, and Garuda in Bahasa and English language that published online from 2012-2022 according to keywords. Of 9.030 studies from databases identified 30 journal studies were included. Literature studies show that the prevalence of elderly women with RA is higher than men. These studies also shows that severity of RA affects the ability of elderly to do a physical activity and physical activity itself influences reducing pain and preventing the severity of RA. The conclusion of this study is that the prevalence of elderly women with RA is higher than men and physical activity is associated with RA. Suggestions for future researchers to focus more on treatments that can be done to reduce the risk of Rheumatoid Arthritis in elderly.